Student Worksheet Development Using the PMRI Approach in the Classroom Context with an Orientation toward Students’ Conceptual Understanding - Nova, Erias; Retta, Allen Marga; Nopriyanti, Tika Dwi (Mathematics Education Journal, 2022)
This research aimed to produce a valid and practical product in the form of a student worksheet using the Indonesian version of the Realistic Mathematics Education (PMRI) approach in the classroom context with an orientation toward students’ conceptual understanding and to figure out the potential effect of the student worksheet developed. It is a piece of development research under the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection was performed using documentation, a questionnaire, and a test. The object of this research was the development of a student worksheet using the PMRI approach within the classroom context with an orientation toward students’ conceptual understanding. Meanwhile, the subjects of the research were students of grade X of SMAN 06 Banyuasin. The research results showed that the student worksheet produced was declared valid (with an average score of 90.83), practical (based on the students’ questionnaire responses, with a score of 79.65), and potentially influential to a high degree (based on the students’ test results, with a percentage of 84%). Therefore, the student worksheet that was developed using the PMRI approach within the classroom context with an orientation toward students’ conceptual understanding was worth using in the learning process.DOI : https://doi.org/10.22342/jpm.16.2.14854.203-214